Fire Risk Situation Analysis in the Nimtoli Area of Old Dhaka - Sahebi, Masaba Tasneem; Rahman, Md Marufur; Rahman, M Maksudur (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Assessment of the fire risk situation of Nimtali area by using eight indicators related to the fire source, fire spreading and evacuation during fire incidents was conducted. The results revealed that none of the buildings has emergency exits, fire protection measures, fire hydrant and provision of a fire drill. The area is densely populated. Most of the buildings are mixed-used and have no space in between. Electrical cables are haphazardly hanging from poles. Access roads are incredibly narrow. By analyzing eight indicators, it is found that the entire Nimtoli area is still at risk of fire hazard. Within Nimtoli, 32% area is at high risk, and 45% is at moderate risk of fire hazard. Proper fire safety measures and safety inspection, regular maintenance of utility lines, awareness about fire hazards among the dwellers, proper implementation of Bangladesh national building code (BNBC) and regulation of mixed-use of buildings can drastically reduce the fire risk in the urban area of Bangladesh. J. Asiat. Soc. Bangladesh, Sci. 46(1): 91-102, June 2020